Viability and adhesion of osteoblast and fibroblast cells on polymethyl methacrylatehydroxyapatite composite scaffold - Karina Kusuma Wardhani; Retno Indrawati Roestamadji; Masami Kanawa; Tania Saskianti; Erin Imaniar Basar; Varellia Awang Wangi Kardikadewi (Faculty of Dental Medicine Universitas Airlangga, 2026)
Introduction: Polymethyl methacrylate (PMMA) and hydroxyapatite (HA) composites are emerging bone graft candidates, combining mechanical stability with osteoconductivity. PMMA contributes to structural strength and handling properties, while HA enhances bioactivity and bone tissue interaction. Prior to clinical use, biocompatibility toward both hard tissue–related cells (osteoblasts) and soft tissue–related cells (fibroblasts) must be established. Purpose: This study aimed to analyze the cell viability and adhesion of osteoblast (hFOB) and fibroblast (BHK-21) cells on a PMMA-HA composite with a 20:80 ratio. Methods: PMMA-HA composite (20:80) scaffolds were synthesized using the freeze-drying method to obtain a porous structure. Cell viability was evaluated using an indirect contact method with the MTT assay after 24 hours of incubation. Surface topography and cell adhesion morphology were analyzed using Scanning Electron Microscopy (SEM). Results: The MTT assay revealed cell viability percentages of 82.55% for hFOB cells and 88.14% for BHK-21 cells, indicating favorable cellular responses to the PMMA-HA composite. SEM analysis demonstrated that the scaffold possessed a rough, irregular, and porous surface. Cell adhesion analysis showed distinct morphological responses: hFOB cells exhibited a spherical morphology adapting to micropores, while BHK-21 cells displayed extensive spreading with flattened morphology and filopodia extensions. Conclusion: The PMMA-HA composite met biocompatibility standards, showing cell viability above 70% according to ISO 10993-5. The scaffold supported cell adhesion with specific morphological adaptations for both cell lines, indicating that the PMMA-HA composite is non-cytotoxic and a potential candidate for bone graft applications.